(untitled) (Pulse, 2023)
Background Sexually Transmitted Infections (STIs) are often diagnosed by clinical symptoms and signs due to lack of sensitive laboratory methods. Most of the time pathogens are not identified and antibiotics are used empirically. The purpose of our study is to find out the STI pathogens detected by sensitive multiplex PCR done routinely in a tertiary care hospital. Materials and methods A total of 578 samples were tested from February 2015 to July 2022. Urine, prostatic secretion, urethral swab, high vaginal swab, semen, throat swabs were collected from symptomatic patients for the routine test. DNA was extracted and Neisseria gonorrhoeae, Chlamydia trachomatis, Mycoplasma genitalium, Trichomonas vaginalis were screened by using CE-IVD approved multiplex Real Time PCR kit. Result Out of 578 cases, 76 (13.15%) were positive for at least one pathogen and 5 were co-infections. Out of 76 positive cases, Chlamydia trachomatis was found 41 (53.9%), Neisseria gonorrhoeae was 13 (17.1%), Mycoplasma genitalium was 12 (15.8%), and Trichomonas vaginalis 5 (6.6%) and co-infections with Neisseria gonorrhoeae and Chlamydia trachomatis was 5 (6.6%). Positivity rate was remarkably higher in male (77.6%) than female (22.4%) and predominant age group was 19-40 years. Conclusion The predominant STIs pathogen found in our cohort is Chlamydia trachomatis followed by Neisseria gonorrhoeae. Multiplex PCR is a wide-ranging diagnostic method for the detection of multiple pathogens simultaneously which allows early and accurate diagnosis of STIs. Pulse Volume 12-14 2020-2022 p.34-39